Pengalaman pasien myasthenia gravis yang menjalani therapeutic plasma exchange - Catur Wijayanti; Dwi Retno Sulistyaningsih; Erna Melastuti (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Myasthenia gravis is a rare autoimmune neuromuscular disorder that significantly impacts patients' quality of life due to fluctuating muscle weakness and the risk of myasthenic crisis. Therapeutic plasma exchange is one of the primary therapies used to manage acute exacerbations by removing pathogenic antibodies from the circulation. Purpose: To explore the lived experiences of patients with myasthenia gravis undergoing therapeutic plasma exchange from physical, psychological, social, cultural, and spiritual perspectives. Method: A qualitative study using a phenomenological approach was conducted involving nine participants diagnosed with myasthenia gravis who had undergone therapeutic plasma exchange more than once. Data were collected through in-depth face-to-face interviews and analyzed using Husserlian phenomenological analysis. Results: Participants reported physical symptoms including ptosis, diplopia, dysphagia, dyspnea, dysphonia, and limb weakness. During the procedure, common complaints were a sensation of coldness and fatigue, while post-therapy improvements included reduced shortness of breath, clearer voice, improved eyelid function, and increased muscle strength. Conclusion: The experiences of patients with Myasthenia Gravis undergoing Plasma Exchange Therapy are multidimensional. Holistic nursing care that addresses physical, psychological, social, cultural, and spiritual aspects is crucial to support treatment success and improve patient outcomes. Keywords: Holistic Nursing Care; Myasthenia Gravis; Phenomenology; Patient Experience; Therapeutic Plasma Exchange. Pendahuluan: Miastenia Gravis adalah gangguan neuromuskular autoimun langka yang secara signifikan memengaruhi kualitas hidup pasien karena kelemahan otot yang berfluktuasi dan risiko krisis miastenia. Pertukaran Plasma Terapeutik adalah salah satu terapi utama yang digunakan untuk mengelola eksaserbasi akut dengan menghilangkan antibodi patogen dari sirkulasi. Tujuan: Untuk mengeksplorasi pengalaman hidup pasien Miastenia Gravis yang menjalani Pertukaran Plasma Terapeutik dari perspektif fisik, psikologis, sosial, budaya, dan spiritual. Metode: Studi kualitatif dengan pendekatan fenomenologis dilakukan yang melibatkan sembilan partisipan yang didiagnosis dengan Miastenia Gravis yang telah menjalani Pertukaran Plasma Terapeutik lebih dari sekali. Data dikumpulkan melalui wawancara tatap muka mendalam dan dianalisis menggunakan analisis fenomenologis Husserlian. Hasil: Partisipan melaporkan gejala fisik termasuk ptosis, diplopia, disfagia, dispnea, disfonia, dan kelemahan anggota tubuh. Selama prosedur, keluhan umum adalah sensasi dingin dan kelelahan, sementara perbaikan pasca-terapi meliputi berkurangnya sesak napas, suara yang lebih jernih, peningkatan fungsi kelopak mata, dan peningkatan kekuatan otot. Simpulan: Pengalaman pasien dengan Myasthenia Gravis yang menjalani Terapi Pertukaran Plasma bersifat multidimensional. Perawatan keperawatan holistik yang menangani aspek fisik, psikologis, sosial, budaya, dan spiritual sangat penting untuk mendukung keberhasilan pengobatan dan meningkatkan hasil pasien. Kata Kunci: Fenomenologi; Myasthenia Gravis; Pengalaman Pasien; Perawatan Keperawatan Holistik; Terapi Pertukaran Plasma.